Intimate Partner Violence Experiences Among Puerto Rican Mothers. Issue 5 (March 2022) - Natal, Maria
This qualitative, transcendental, phenomenological study explored the subjective experiences of Puerto Rican mothers, aged 18 and older, who experienced intimate partner violence (IPV) and their perceptions of how provider and law enforcement approaches to screening impacted disclosure. Participant recruitment was coordinated with gatekeepers, and community and domestic violence organizations, who posted bilingual flyers. A total of nine Puerto Rican woman aged 18 and older who experienced IPV participated and agreed to consent to audio-recorded interviews. Data analysis integrated content and thematic procedures, including transcribing, reading, auditing, and coding the interviews based on statements, quotes, and sentences, then grouped into themes that captured the essence of their lived experiences. The IPV was perpetrated primarily by the children's biological fathers and escalated over time. Four of the eight participants (one was lost to follow-up) had been screened while seeking medical care for IPV-related injuries, two disclosed their IPV, and one of the two was provided with a referral for IPV resources. All had multiple previous encounters with law enforcement but were afraid and ashamed to disclose the IPV. Lack of disclosure was associated with Hispanic cultural values and norms that included collectivism or keeping group cohesiveness, familism that socially emphasizes the family unit, marianismo as an ascribed female gender role of self-sacrifice and caregiving, and threats that their children would be removed from the home. Most of the women did not have knowledge of resources available to them and wanted to keep the family unit together. All believed they would be blamed for the incidents. Major implications include the need for multilanguage and multimedia campaigns to improve access to information, transparency with IPV screenings that may influence IPV disclosure, and systemwide education that addresses mother-blaming.